Regulation effect of fiscal subsidies for agriculture on farmland abandonment: empirical evidence from China - Li, Jungao; Li, Junsong; Lin, Zhijian (Frontiers in Sustainable Food Systems, 2025)
An examination of the evolution and underlying patterns of China’s fiscal agricultural subsidy policies since the beginning of the new century reveals that these subsidies have played a measurable role in curbing the abandonment of cultivated land. This study employs a neoclassical growth model to theoretically examine how fiscal subsidies for agriculture influence farmland abandonment. Using panel data from 2003–2020 across 30 Chinese provinces, the study employs static panel and dynamic panel fixed effect models to assesses the effects of fiscal subsidies for agriculture on both the intensity of farmland abandonment and the actual multiple cropping index. The findings reveal that: fiscal subsidies for agriculture contribute to an increase in actual multiple cropping areas and effectively reduce the abandonment intensity of cultivated land; farmland abandonment demonstrates a degree of path dependence, with past levels influencing current rates; the regulatory impact of fiscal subsidies for agriculture on farmland abandonment is influenced by mechanization levels, natural conditions, and agricultural employment population. Specifically, regions with higher agricultural mechanization levels, favorable natural conditions, and larger agricultural populations exhibit greater efficacy in curbing farmland abandonment. This study provides developing countries with a reference framework for formulating targeted policies to manage farmland abandonment.